2007
DOI: 10.1063/1.2774002
|View full text |Cite
|
Sign up to set email alerts
|

Surface acoustic wave depth profiling of a functionally graded material

Abstract: The potential and limitations of Rayleigh wave spectroscopy to characterize the elastic depth profile of heterogeneous functional gradient materials are investigated by comparing simulations of the surface acoustic wave dispersion curves of different profile-spectrum pairs. This inverse problem is shown to be quite ill posed. The method is then applied to extract information on the depth structure of a glass-ceramic ͑ alumina͒ functionally graded material from experimental data. The surface acoustic wave analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 24 publications
(24 reference statements)
0
16
0
Order By: Relevance
“…When polarization selective detection is done, even information about the rotational relaxation can be extracted [7]. Also, in the reflection mode, the signal-to-noise ratios achieved by ISS in the heterodyne detection mode are quite satisfactory [1,2,28,31], even for rough samples [32].…”
Section: Resultsmentioning
confidence: 99%
“…When polarization selective detection is done, even information about the rotational relaxation can be extracted [7]. Also, in the reflection mode, the signal-to-noise ratios achieved by ISS in the heterodyne detection mode are quite satisfactory [1,2,28,31], even for rough samples [32].…”
Section: Resultsmentioning
confidence: 99%
“…32 TG spectroscopy with changing analysis depths has been used to reconstruct depth profiles of Rayleigh wave velocity and elastic constants. 35,36 TG spectroscopy was also used to determine the thickness of amorphized layers of ion-implanted silicon, 37 simultaneously acquiring the layer's density, Young's modulus, and Poisson's ratio. Similar changes were investigated in lithium niobate thin films during ion implantation, 17 suggesting that TG spectroscopy is equally viable as an in situ technique, with the added advantage of being a noncontact method.…”
Section: Potential Methods For Mechanical Spectroscopy Of Radiation Dmentioning
confidence: 99%
“…For thermal grating decay, Käding (42) showed that the measurement is sensitive to thermal properties up to a depth of L/π, while a surface layer of thickness L/2 dominates the measured SAW signal (44). This ability to target different probing depths makes TGS measurements very attractive for selectively probing the properties of thin surface regions, or even depth profiling of properties (45). TGS is particularly useful for studying ion irradiation as it allows probing of the properties of the ion-irradiated layer alone, typically on the same order in thickness as the TGS probe depth, with little contribution from the unirradiated material beneath.…”
Section: )mentioning
confidence: 99%